Firms, Industries, and Unemployment Insurance: An Analysis Using Employer-Employee Data - Miles Corak; Wen-Hao Chen (Institute for the Study of Labor (IZA), 2003)
Administrative data on the universe of employees, firms, and unemployment insurance (UI) recipients in Canada over an 11 year period are used to examine the operation of UI using the firm as the unit of analysis. Persistent transfers through UI are present at both industry and firm levels, and an analysis using firm fixed effect indicates that an important fraction of variation in them can be attributed to firm effects. Calculations of overall efficiency loss are very sensitive to the degree to which firm level information is used. A full appreciation of how UI interacts with the labour market requires recognition of the characteristics and human resource practices of firms.
Keywords: H25; J65; 330; unemployment insurance; payroll taxes; Arbeitslosenversicherung; Sozialversicherungsbeitrag; Subvention; Branche; Schätzung; Kanada